Outage Detection Unit for Smart Monitoring of Electric Supply - Gupta, Saurabh (International Journal of Computer Sciences and Engineering, 2025)
This paper presents a cost effective product to automatically monitor and detect outages in villages who don’t have a reliable and intermittent supply of electricity. This product might prevent malpractices and corruption that linemen do by avoiding outage complaints and delaying the whole process, and hence, make the electric supply trustworthy.